Hydrogen Embrittlement Behavior at Different Strain Rates in Low-carbon Martensitic Steel. (2015) - Momotani, Y.; Shibata, A.; Terada, D.; Tsuji, N.
Abstract: This study investigated hydrogen embrittlement behavior in a low-carbon martensitic steel by uniaxial tensile test at different strain rates. With increasing the strain rate, fracture surface morphology changed from intergranular-like manner at prior austenite grain boundaries to ductile one inside prior austenite grains. The hydrogen microprint treatment revealed that hydrogen tended to accumulate mainly on prior austenite grain boundaries when the strain rate was low. On the other hand, in the case of higher strain rate, hydrogen distribution was rather uniform presumably because there was no enough time for hydrogen to accumulate on prior austenite grain boundaries during the tensile test. Accordingly, we concluded that the change of hydrogen-related fracture manner with increasing the strain rate was due to the difference in the hydrogen accumulation behavior.